Structural and biophysical characterization of the major proteins from the seminal plasma of Dorper rams - da Silva, Luan Sitó; Ruivo, Maycon Araújo; da Cruz, Tainá Michelle; Meneguello, Jean Eduardo; Pilau, Eduardo Jorge; Caruso, Ícaro Putinhon [UNESP]; de Moraes, Gentil Vanini; Martinez, Antônio Campanha; Seixas, Flavio Augusto Vicente (Elsevier, 2021)
Pregnancy rates using frozen semen from rams are higher than for horses. One of the factors that positively influences this effect is the composition of low-molecular-weight proteins from seminal plasma, since the amounts of these proteins are much lower in horses. The aim of this work was to purify the major protein components from ram seminal plasma for structural and biophysical characterization. First, the ram semen was collected and the plasma separated by centrifugation. The protein fractions were isolated by gel filtration chromatography, analyzed by circular dichroism spectroscopy and the amino acid sequence identified by mass spectrometry (LC-MSE), the results of which were used to model the protein structure by bioinformatics techniques. This protein was identified by LC-MSE as a spermadhesin, being an unglycosylated monomer with Tm = 69.3 °C and ΔHm = 371 kJ mol−1 at pH 7.0. This work describes for the first time the structural characterization of a spermadhesin from seminal plasma of Dorper rams.
Keywords: Animal reproduction; Protein; Sheep; Spermadhesin